High‐Quality Black Phosphorus Atomic Layers by Liquid‐Phase Exfoliation. (2nd February 2015) - Yasaei, Poya; Kumar, Bijandra; Foroozan, Tara; Wang, Canhui; Asadi, Mohammad; Tuschel, David; Indacochea, J. Ernesto; Klie, Robert F.; Salehi‐Khojin, Amin
Abstract : Recent isolation of black phosphorus atomic layers (known as phosphorene) has revealed its great potential for use as an alternative 2D semiconductor in many areas of electronics and optoelectronics. Liquid‐phase exfoliation is utilized to produce high‐quality black phosphorus nanoflakes with thicknesses down to a monolayer in the form of uniform and stable dispersions, allowing for pace toward practical applications.